Beyond the blog: The networked self of travel bloggers on Twitter - Azariah, Deepti (ANZCA, 2011)
Studies of the use of social media in tourism rarely discuss various tools in conjunction with each other. The growth of Twitter has attracted the attention of tourism researchers interested in the platform as a marketing tool and a source of information about consumers (Claster, Cooper, & Sallis, 2010; Hay, 2010). Similar studies of travel blogs largely focus on what tourists say about destinations and their own experiences (Akehurst, 2009; Bosangit, McCabe, & Hibbert, 2009; Schmallegger &Carson, 2008). Blogs in general, and travel blogs in particular, are widely regarded as providing credible information about their authors. Both the content and formal features of these online narratives shape the self-presentation and positioning of their authors as bloggers. Given that blogs are increasingly “distributed” (Helmond, 2010) and that independent travel bloggers often link to other platforms, it is necessary to consider author-created content beyond the blog to understand the presentation of what Papacharissi (2010) calls a “networked self”. Drawing on the theories of Bakhtin and Goffman, which have informed previous analyses of blogs, and Dann’s (1996) concept of tourist discourse, this paper argues that the Twitter pages of independent travel bloggers extend the self-presentation in their blogs.In particular, it focuses on how travel bloggers use specific conventions, formal features, and narrative techniques of Twitter to express a networked self and reiterate themes of the blog. Through a random selection and textual analysis of various messages it finds that while there is some mention of the travel experience, the various conventions and conversations on Twitter are self-presentational elements that generally strengthen the authors’ position as travel bloggers. The characteristic narrative techniques of Twitter also reveal tensions between the discourses of travel and tourism. The networked self of the independent travel blogger is negotiated in these discursive tensions.